Purified Vero Cell Rabies Vaccine (PVRV, Verorab(®)): A Systematic Review of Intradermal Use Between 1985 and 2019 - Moulenat, Thomas (Trop Med Infect Dis, 2020)
The purified Vero cell rabies vaccine (PVRV; Verorab(®), Sanofi Pasteur) has been used in rabies prevention since 1985. Evolving rabies vaccination trends, including shorter intradermal (ID) regimens with reduced volume, along with WHO recommendation for ID administration has driven recent ID PVRV regimen assessments. Thus, a consolidated review comparing immunogenicity of PVRV ID regimens during pre-exposure prophylaxis (PrEP) and post-exposure prophylaxis (PEP) is timely and beneficial in identifying gaps in current research. A search of seven databases for studies published from 1985 to November 2019 identified 35 studies. PrEP was assessed in 10 studies (n = 926) with 1–3-site, 1–3-visit regimens of up to 3-months duration. Seroconversion (rabies virus neutralizing antibodies [RVNA] ≥ 0.5 IU/mL) rates of 90–100% were reported within weeks, irrespective of regimen, with robust booster responses at 1 year (100% seroconversion rates by day 14 post-booster). However, data are lacking for the current WHO-recommended, 2-site, 1-week ID PrEP regimen. PEP was assessed in 25 studies (n = 2136) across regimens of 1-week to 90-day duration. All ID PEP regimens assessed induced ≥ 99% seroconversion rates (except in HIV participants) by day 14–28. This review confirms ID PVRV suitability for rabies prophylaxis and highlights the heterogeneity of use in the field.